PENGARUH KEPEMILIKAN SMARTPHONE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI SMA NEGERI DI KABUPATEN SLEMAN YOGYAKARTA - Bahrin Bahrin; Ummi Kalsum; Duharman Duharman (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study aims to determine the effect of smartphone ownership on student learning outcomes in Economics subjects among grade XI students of public senior high schools in Sleman Regency, Yogyakarta. This research employed a quantitative approach using a survey method. The population consisted of all grade XI students in public senior high schools in Sleman Regency. A total of 104 students were selected as research samples using quota sampling techniques. Data were collected through questionnaires and documentation. Data analysis was conducted using simple linear regression. The results revealed that smartphone ownership had a positive and significant effect on student learning outcomes. This finding was indicated by a significance value of 0.011 < 0.05 and a regression coefficient of 1.735. The coefficient of determination was 27.8%, indicating that smartphone ownership contributed 27.8% to student learning outcomes, while the remaining percentage was influenced by other factors outside this study. Therefore, better smartphone utilization tends to improve students’ learning outcomes.